MUNICIPAL PUBLIC MANAGEMENT, PUBLIC POLICIES, INNOVATIVE PRACTICES, AND SMART FINANCING: AN EXPERIENCE REPORT FROM BETT NORTHEAST - de Castro, Ana Cristina; de Almeida, Isabel Cristina Pereira Dantas (Seven Editora, 2026)
Municipal public management plays a strategic role in the implementation and execution of educational public policies in an innovative way and with intelligent financing. Faced with contemporary challenges such as budgetary constraints, growing social demands, and the need for transparency, it becomes essential for municipalities and municipal education departments to adopt innovative practices and intelligent financing models as a possible path to guarantee quality public education. This article discusses and presents the main dimensions of educational public management, emphasizing the importance of well-planned public policies and, through effective pedagogical projects, ensuring the expansion and provision of Full-Time Schooling, Youth and Adult Education, and Special and Inclusive Education in municipal public education networks.